2014
DOI: 10.1186/1471-2393-14-165
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community determinants of neonatal mortality in Ghana: a multilevel analysis

Abstract: BackgroundNeonatal mortality is a global challenge; identification of individual and community determinants associated with it are important for targeted interventions. However in most low and middle income countries (LMICs) including Ghana this problem has not been adequately investigated as the impact of contextual factors remains undetermined despite their significant influence on under-five mortality and morbidity.MethodsBased on a modified conceptual framework for child survival, hierarchical modelling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
93
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 36 publications
23
93
1
1
Order By: Relevance
“…The finding, however, that mortality was significantly higher in rural neonates (NMR, 36 deaths per 1000 live births) compared with urban neonates (NMR, 28 deaths per 1000 live births) possibly reflects socioeconomic disparity. This urban advantage agrees with the general trend in the literature . For example, a previous UNICEF analysis has shown that birth in the rural areas is a significant risk factor for neonatal mortality .…”
Section: Discussionsupporting
confidence: 90%
“…The finding, however, that mortality was significantly higher in rural neonates (NMR, 36 deaths per 1000 live births) compared with urban neonates (NMR, 28 deaths per 1000 live births) possibly reflects socioeconomic disparity. This urban advantage agrees with the general trend in the literature . For example, a previous UNICEF analysis has shown that birth in the rural areas is a significant risk factor for neonatal mortality .…”
Section: Discussionsupporting
confidence: 90%
“…Advanced maternal age is a well‐established risk factor for stillbirths and it is linked with a higher prevalence of chronic hypertension and placental pathologies . Advanced maternal age was a risk factor for neonatal deaths regardless of parity, consistent with some previous findings but in contrast to several others . The association may be due to age‐related birth complications resulting in early neonatal deaths, or less health‐seeking behaviour and more observance of potentially harmful traditions among older generations.…”
Section: Discussionsupporting
confidence: 87%
“…Reviews suggest that stillbirths and neonatal deaths are linked to several biological and socio‐economic risk factors . While some studies set in sub‐Saharan Africa have been published, mostly from Ethiopia , and Ghana , a dearth of population‐level studies remains. An estimated 57% of deliveries in sub‐Saharan Africa take place outside health facilities , rendering hospital‐based studies unrepresentative.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25] Lastly, low birth weight was identified as a risk factor for neonatal mortality; which was also highlighted in other studies. 2,8,14,15,[26][27][28][29] Newborns with low birth weight are likely to have multiple complications, ranging from metabolic disorders to neurological and sensory disorders, sometimes irreversible.…”
Section: Risk Factors For Neonatal Mortalitymentioning
confidence: 61%